RHETORICAL MOVES ANALYSIS ON SCOPUS-INDEXED RESEARCH ARTICLE ABSTRACTS BY NATIONAL AND INTERNATIONAL AUTHORS - Ananta Buana Nurcik; Eri Kurniawan; Arif Husein Lubis (University of Kuningan, 2022)
Abstracts in research articles are important for readers in determining whether to continue reading the article or not. A plethora of studies involving abstracts’ rhetorical moves has previously been published, but scant attention has been given to the relationship between the rhetorical moves and authors’ nationalities. This study is aimed at comparing the rhetorical moves and linguistic realizations of abstracts by authors of different nationalities. This study analyzed 30 hard sciences abstracts written by national and international authors published in the International Journal of Science and Technology (IJoST). Hyland’s (2000) model of rhetorical moves was employed as the framework of analysis. Findings showed that both groups similarly spent more space in manifesting the method and findings moves. However significant differences were evident in the steps of the introduction and method moves. National authors considered the conclusion move as optional, whereas the other moves in both groups were considered conventional. International authors considered topic generalization step as conventional, while all other steps in the introduction move of both groups were optional. No difference was found in the voices used. However, tense-wise, the international authors favored present tenses in describing the research purpose while the national authors favored past tenses. This study concludes that the differences in the rhetorical organizations between the international and national authors can mostly be found in the steps, instead of the moves. Additionally, as the use of voice does not show any difference, the use of different tenses in each move distinguishes the two groups of authors.